Cognitive Behavioral Training Reduces Socially Anxious Classroom Behavior in Primary School Students - Casale, Gino; Haarhoff, Daniel (Frontiers in Education, 2022)
Many students show symptoms of social anxiety. Cognitive behavioral training (CBT) has been shown to be effective in reducing symptom behavior in therapeutic and school contexts, but there are hardly any single-case studies that examine the individual effectiveness in school settings. Furthermore, the extent to which differential responsivity effects are exhibited by students has not been examined yet. This single-case study with AB design investigates the effects of a CBT on the socially anxious classroom behavior of students with severe symptoms of social anxiety. Two female and two male students (9 to 10 years old) of an inclusive primary school in Germany participated in the CBT over a period of 12 weeks. Socially anxious behaviors were measured daily with Direct Behavior Rating-Multi Item Scales. Visual analyses, overlap indices, and regression models show a substantial behavioral improvement for all students during the intervention. However, there are differences between the students in terms of which specific behaviors were improved and whether the behavioral improvements took place immediately after the implementation of the intervention or continuously from measurement to measurement in the B phase. The results highlight the relevance of specific and individualized behavioral goals for CBT in school, although the effects should be replicated in experimental studies.